Pd-catalyzed arylation of linear and angular spirodiamine salts under aerobic conditions. Issue 5 (1st February 2017) - Reilly, Sean W.; Bryan, Nikaela W.; Mach, Robert H.
Graphical abstract: Highlights: Efficient arylation of sterically congested spirodiamine compounds is demonstrated. Protocol does not require anhydrous solvents or inert atmosphere. Good to modest yields obtained with electron rich aryl halides in just 20 min. Abstract: Application of Buchwald-Hartwig catalysis for development of biologically relevant arylspirodiamine compounds is reported. This synthetic methodology requires no inert atmosphere and affords yields up to 93% in just 20 min. Linear and sterically hindered angular spirodiamines in salt and free-base form are coupled with electron-rich and -withdrawing aryl chlorides, demonstrating a broad scope and applicability of this protocol.